Autonomy need-based experiences and hope and fear components of autonomy strength: Investigating the longitudinal and reciprocal effects over a two-year period. (February 2023) - Deng, Yanhe; Zhang, Yifei; Zhu, Yijie
Abstract: Preliminary research operationalized autonomy strength narrowly as hope for autonomy satisfaction, while neglecting to consider fear of frustration as an important source of motivation. However, developmental antecedents and outcomes of hope and fear components of motives are distinct. Thus, we took a differentiate perspective on autonomy strength, which proposed fear of being controlled as a fear component, to comprehensively investigate whether a reciprocal relationship exists between autonomy-based experiences and autonomy strength. The current findings supported for some of the key predictions from the proposed interplay using longitudinal data collected in 2 years. Specifically, we found these transactional processes of autonomy-satisfying experiences with autonomy valuation and autonomy-frustrating experiences with autonomy desire over 2 years. Fear of being controlled predicted subsequent increases in autonomy frustration and decreases in autonomy satisfaction after 2 years, but not vice versa. This study provides valuable insights into autonomy strength and highlights the transactional process between autonomy-based experience and autonomy strength. Highlights: Autonomy valuation positively interplayed with autonomy satisfaction during 2 years. Autonomy desire and autonomy frustration mutually reinforced each other during 2 years. Fear of being controlled led to more autonomy frustration, and less satisfaction after 2 years.